2006
DOI: 10.1128/iai.74.5.3030-3034.2006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the BBA68 Protein (BbCRASP-1) of the Lyme Disease Spirochetes Does Not Contribute to Factor H-Mediated Immune Evasion in Humans and Other Animals

Abstract: BBA68 (BbCRASP-1) of the Lyme disease spirochetes binds human factor H (FH) and FH-like protein 1 (FHL-1).Here we assess transcription of the BBA68 gene and production of BBA68 in infected mice and humans using real-time reverse transcriptase PCR and immunoblotting. The species specificity of FH binding to BBA68 was also tested. The data suggest that BBA68 does not play an important role in immune evasion in animals.The Lyme disease spirochete, Borrelia burgdorferi, can bind the human complement regulatory pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
57
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 30 publications
7
57
1
Order By: Relevance
“…In contrast, cspA transcripts become undetectable within two weeks of establishing mammalian infection Lederer et al, 2005;McDowell et al, 2006;Bykowski et al, 2007). Humans and laboratory mice produce limited antibody responses to BbCRASP-1, consistent with brief exposure of that protein to host immune systems .…”
Section: Disseminated Mammalian Infectionmentioning
confidence: 99%
“…In contrast, cspA transcripts become undetectable within two weeks of establishing mammalian infection Lederer et al, 2005;McDowell et al, 2006;Bykowski et al, 2007). Humans and laboratory mice produce limited antibody responses to BbCRASP-1, consistent with brief exposure of that protein to host immune systems .…”
Section: Disseminated Mammalian Infectionmentioning
confidence: 99%
“…B. afzelii and B. garinii, which are generally more sensitive to complement (5,20,40), produce fewer FHBPs. Some FHBP-encoding genes are environmentally regulated (10,26,31,39), and the proteins they encode have been shown to have differing binding specificities for members of the FH protein family (19,24,34). Recent work has demonstrated that FHBPs can also bind to a series of serum proteins (16,26,35).…”
mentioning
confidence: 99%
“…One or more OspE paralogs have been demonstrated to be expressed during infection in ticks and mammals, indicating that they may carry out important functions in these environments (16-18, 20, 32-34, 38). Interestingly, while BBA68 has clear factor H/FHL-1 binding ability, it is not expressed during infection; thus, its role in pathogenesis is unclear (6,26,42,43).…”
mentioning
confidence: 99%